2017
DOI: 10.17093/alphanumeric.334239
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Service Quality At Tax Chambers by SERVQUAL Analysis

Abstract: The aim of the research is to come out the difference between expected service and perceived service at Tax Chamber that taxpayers get service. SERVQUAL Scale was conducted to 90 people who get service from X Tax Chambers between April-May 2016. As a result of the SERVQUAL analysis, the research reveals that the taxpayers of the X Tax Chambers are not satisfied with the service quality and the most difference between expected service quality and perceived service quality is accessibility dimension. The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The outcomes of this research are in line with research performed by Arı et al (2017), discovering that there is no distinction between the expected provider with the carrier perceived with the aid of the taxpayer.…”
Section: The Effect Of Properly Carrier On Taxpayer Awarenesssupporting
confidence: 81%
See 2 more Smart Citations
“…The outcomes of this research are in line with research performed by Arı et al (2017), discovering that there is no distinction between the expected provider with the carrier perceived with the aid of the taxpayer.…”
Section: The Effect Of Properly Carrier On Taxpayer Awarenesssupporting
confidence: 81%
“…Several studies: good service is carried out by (Masunga et al, 2020) the great of carrier and information has a brilliant impact on creating a wish to acquire and utilize an e-tax device that improves tax compliance behavior. However, the first-rate device has not shown an enormous impact on tax compliance behavior (Arı et al, 2017). The study showed huge variations between carrier perceptions and demographic features.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study aims to focus on the factors affecting the decision of a customer while booking a hotel using SERVPERF scale. SERVPERF is a performance only scale and is believed to be a preferable tool for reliability and validity as it only takes into consideration the perceived service quality and does not ponder upon the expected service quality [3]. (Brady, 2002) suggested that service performance only (SERVPERF) scale can be used to determine the overall service quality, in contradiction to the difference between expectations and perceptions based SERVQUAL scale.…”
Section: Introductionmentioning
confidence: 99%